Effects of shame in the workplace in Chinese culture. - Wong, Shi Qi. (2010)
Studies have shown that shame in the workplace has a significant negative impact on an individual’s functioning at work due to the unpleasant feelings shame elicits. In the present study, however, the effects of shame were being explored to learn more about the possible positive interpersonal function shame serves and the conditions that determine the choice between positive and negative behaviours. Given that most Chinese value social harmony and interpersonal relationships, it was hypothesized that following a shame-producing face loss situation, restorative behaviours would be exhibited by the employees in order to preserve the affected workplace relationships. Information derived from 19 qualitative interviews with Chinese working adults (mean age = 23.58) is used to draw inferences about the interpersonal function of shame and the conditions under which positive behaviours will be elicited due to shame. From the study, shame, an unpleasant emotion, is found to be functional when the situation is perceived to be of slight severity and the consequences of exhibiting negative behaviours are dire in the workplace.